Academic opportunities for talented athletes in slovenian secondary schools - Jurak, Gregor (Kinesiologia Slovenica, 2005)
A sample of 86 potentially succesful secondary school athletes was analysed to examine how they co-ordinate their academic and sporting commitments. A questionaire was constructed for the purposes of the research. The collected data were analysed using discriminant analysis, t-test for independent samples and relevant correlation coefficients. Results showed that Slovenian secondary school athletes are succesful in co-ordinating their academic and sporting obligations. Despite their frequent absence from school the overall final school results of athletes do not vary from those of the general population. The pre-announcement of oral exam dates and the tolerance of frequent absence from the academic process are some of the sistematic solutions that are most commonly used in schools. Surprisingly, a high proportion of sample does not use any organised special learning assistance, supplementary learning materials or the distance learning via the internet to fulfil their academic commitments, even when they are available. However results showed that support is needed because there is a negative correlation between the extent of absence from school and the final results of mathematics exams. The analysis furthermore shows that there is a noticable, yet statistically insignificant influence of absence from the academic process on the overall final school results. Organisationally speaking, the most efficient ways to coordinate academic and sporting obligations are offered in special sports classes in gymnasiums.
Keywords: dijaki; srednja šola; učni uspeh; vrhunski šport